Blue light regulates the accumulation of two psbD-psbC transcripts in barley chloroplasts. - Gamble, P E (1989)
Synthesis of D2, a Photosystem II reaction center protein encoded by psbD, is differentially maintained during light-induced chloroplast maturation. The continued synthesis of D2 is paralleled by selective light-induced accumulation of two psbD-psbC transcripts which share a common 5' terminus. In the present study, we examine the nature of the photoreceptor and the fluence requirement for psbD-psbC transcript induction. The light-induced change in psbD-psbC RNA population can be detected between 1 and 2 h after 4.5 day old dark-grown barley seedlings are transferred to the light. Light-induced transcript accumulation occurs normally in the chlorophyll-deficient barley mutant, xan-f10, indicating that light-activated chlorophyll formation and photosynthesis are not required for RNA induction. High fluence blue light fully induces psbD-psbC transcript accumulation; low or high fluence red or far-red light do not. However, psbD-psbC transcript accumulation elicited by blue light pulses can be partially attenuated if far-red light is given immediately following the blue light treatment. Thus, although blue light is needed to initiate transcript accumulation, phytochrome modulates the amplitude of the response. Pretreatment of dark-grown plants with cycloheximide blocks light-induced psbD-psbC transcript accumulation. This could implicate a blue-light responsive nuclear gene in the light-induced accumulation of the two psbD-psbC transcripts.